Self-tuning Core-less Serial Resonant DC/DC Converter for Powering Loads on Rotating Shafts - Apse-Apsitis, P.; Avotins, A.; Ribickis, L. (Elektronika ir Elektrotechnika, 2013)
To feed sensors on different turning or rotating shafts of electrical motors, like servo, stepper or DC motor shafts, pan/tilt and different robotic system rotating parts, especially where rotations are up to 3600 and more turns of rotation, conventional wire loop cannot be applied. The same problem also lies with data transmission from sensor. The article describes a way to transfer energy wirelessly from stationary part to rotating (moving) part to solve the problem with power supply and proposed topology allows wireless data transmission, allowing significantly reduce total systems overall complexity and price. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3466